Assembly point and foothold for contemporary art museums - Ksenia N. Kalashnikova; Anna A. Prozorova (Управление культурой)
Contemporary art museums are currently experiencing a period of turbulence, also related to the consequences of the COVID-19 pandemic and political processes happening in the country. The changes caused by these events affect not only the nature of the exhibited objects, but also the format of the contemporary art museum itself. For example, some of them no longer engage in exhibition activities - is it correct to continue calling them museums? What are the components of the network space of the contemporary art museum that ensure the unity and stability of the network? Conceptually, the study is based on actor-network theory and P. Bourdieu's approach. In such a theoretical framework, the museum is represented as a set of (im)material objects and resources, among which it is possible to identify elements that provide assembly and foothold for the entire space, in other words, the core of sustainable relationships. The sources of information were the results of a series of expert interviews with representatives of the contemporary art industry, an online survey of regular visitors, and content analysis of contemporary art museum websites. The components of the core of sustainable relationships are not the exhibits themselves, but the resources and objects of contemporary art museums that provide communication. Moreover, communication with art is also important, which is carried out through lectures, performances, art mediation, and with people. The leading element in the positioning the museum becomes its role as a place for meetings and communication. At the non-material level of the network, there is also a metaphor - the idea of freedom, which manifests itself in the atmosphere of exhibition spaces through addressing resonating themes and creating multiple images, as well as thanks to flexibility in interaction with exhibits and interpreting their meanings. The stability of the museum is disrupted if the practices related to the core of sustainable relationships cease to be implemented. This can not only explain recent cases of the closure of contemporary art museums but also adaptive measures aimed at maintaining the integrity of museums. Among such measures, greater emphasis can be placed on the communicative component of exhibition spaces.